ENCICLOPEDIA UNIVERSAL ILUSTRADA EUROPEO-AMERICANA (ESPASA-CALPE, 1930)
CONTENIDO: TODOS LOS VOLUMENES SON APENDICES V. 1 A-BECH. -- V. 2 BED-CEO. -- V. 3 CER-DEM. -- V. 4 DEN-EZT. -- V. 5F-HOK. -- V. 6 HOL-MARCH. -- V. 7 MARD-OZ. -- V. 8 P-REE. -- V. 9 REF-SZ. -- V. 10 T-ZYZ